How Do Environmental Quality, Economic Growth, Population Dynamics, Poverty, Rice Productivity, and Coastal Geography Shape Food Security in Southeast Sulawesi Province, Indonesia? - Lukman Yunus; La Ode Alwi; Munirwan Zani; Samsul Alam Fyka; Yusriadin Yusriadin (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Food security remains a critical development challenge, particularly in regions facing complex environmental, socio-economic, and geographical constraints. This study aims to analyze the development of food security and examine the determinants influencing the Food Security Index (IKP) in Southeast Sulawesi Province, Indonesia, during the 2018–2023 period. The analysis uses balanced panel data from 17 districts/cities, sourced from official publications of the Central Statistics Agency (BPS). The dependent variable is the Food Security Index (IKP). In contrast, the explanatory variables include the Environmental Quality Index (IKLH), economic growth, population growth, poverty rate, rice productivity, and the proportion of coastal villages/subdistricts. Descriptive analysis and panel data regression were employed, with the Random Effect Model (REM) selected as the best estimation approach based on the Lagrange Multiplier test. The results indicate that the average IKP in Southeast Sulawesi increased over the study period, reflecting overall improvement in food security, although substantial disparities across districts persist. Regression results indicate that population growth, poverty, and coastal geographic characteristics have adverse, significant effects on food security, while rice productivity has a positive, significant impact. In contrast, environmental quality and economic growth do not exhibit statistically significant effects on the IKP during the study period. The model explains 27.57% of the variation in regional food security, highlighting the importance of demographic, socio-economic, productivity, and geographical factors. These findings suggest that improving food security in Southeast Sulawesi requires integrated policies that prioritize poverty reduction, population pressure management, enhancement of staple food productivity, and context-specific strategies for coastal areas, supported by inclusive and sustainable development approaches. This study contributes to the multidimensional interaction of factors shaping food security at the regional level.